Analysis of Teachers’ Perceptions on the Values of Local Wisdom in the Implementation of Biology Learning - Pahlevy, Alif Reza; Dewi, Nur Kusuma; Alimah, Siti (Universitas Negeri Semarang, 2022)
Scientific learning can be realized with local wisdom-based learning that elaborates Biology learning materials with local wisdom in the school environment. The aim of this study was to analyze the perceptions of Biology teachers about the implementation of local wisdom-based learning on ecosystem materials. The research method was a Pre-Experimental Design approach with the type of One-Shot Case Study. The sample in this study were Biology teachers of grade 10 from three schools in Grobogan Regency.1) Biology learning devices based on local wisdom on ecosystem materials were stated to be very valid so that they could be used for research. Teachers have enthusiasm and interest in the implementation of local wisdom-based learning. The teacher's perceptions of biology learning tools based on local wisdom of ecosystem materials which were implemented in the learning process have very positive criteria. The teachers have enthusiasm for local wisdom-based biology learning to be implemented in biology learning in other materials. Teachers agree that local wisdom-based biology learning is very beneficial for the formation of students' characters and personalities. The teachers think that the integration of local wisdom in biology learning is very good even though there are technical obstacles experienced in the field. Based on the results of the study, it can be concluded that learning biology based on local wisdom has gained teachers’ attraction to implement in the learning process. More in-depth research is needed to define the types of local wisdom in Grobogan Regency that can be implemented in other biology learning materials.